Analysis of 66 patients definitive with transfusion‐associated graft‐versus‐host disease and the effect of universal irradiation of blood. Issue 6 (8th October 2013) - Uchida, S.; Tadokoro, K.; Takahashi, M.; Yahagi, H.; Satake, M.; Juji, T.
SUMMARY Background Transfusion‐associated graft‐versus‐host disease (TA‐GVHD) is a potentially fatal adverse reaction to blood transfusion. Although TA‐GVHD was formerly considered to be rare and to occur only in immunocompromised patients, it was confirmed to occur even in immunocompetent patients in Japan, based on a definitive diagnostic test for TA‐GVHD using highly polymorphic microsatellite repeat sequences. We clarify the clinical picture of TA‐GVHD via definitive diagnosed cases and argue the validity of blood irradiation for TA‐GVHD prevention. Patients and methods Two‐hundred and ninety patients who were suspected of having TA‐GVHD and referred to us for diagnostic testing from October 1992 to August 1999 were analysed for the associated clinical characteristics and risk factors. Effects of universal irradiation were followed up until 2010. Results Sixty‐six of the 290 study patients were diagnosed as having definite TA‐GVHD by microsatellite DNA analysis. Regarding the symptoms of patients with definite TA‐GVHD, a fever of over 38 °C, erythema and leucocytopenia were found in virtually all of these patients. Among patients in whom human leucocyte antigen (HLA) typing was carried out, TA‐GVHD almost always developed in HLA heterozygous patients following the transfusion of HLA homozygous blood. TA‐GVHD was reported significantly more frequently in older patients. In this study, TA‐GVHD was caused by the transfusion of HLA one‐way match blood stored for 14 days. Conclusion No cases of TA‐GVHD development have been confirmed since 2000, when the supply of irradiated blood products became widespread. No major problems have been encountered since the start of universal irradiation, more than 10 years ago.